2015
DOI: 10.1103/physreve.91.050105
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation versus percolation: Scaling criterion for failure in disordered solids

Abstract: One of the major factors governing the mode of failure in disordered solids is the effective range R over which the stress field is modified following a local rupture event. In a random fiber bundle model, considered as a prototype of disordered solids, we show that the failure mode is nucleation dominated in the large system size limit, as long as R scales slower than L(ζ), with ζ=2/3. For a faster increase in R, the failure properties are dominated by the mean-field critical point, where the damages are unco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 25 publications
3
63
0
Order By: Relevance
“…affecting a total of R 2 fibers). Redistributions that affect a finite range are expected to be captured by this process, which is also the case for catastrophic failure [22]. The two extreme cases are the nearest neighbor (R = 1) and mean-field (R L, where L is the system size) interactions and we find a crossover length scale R c above which the system starts behaving like the mean-field limit.…”
Section: Modelmentioning
confidence: 56%
See 2 more Smart Citations
“…affecting a total of R 2 fibers). Redistributions that affect a finite range are expected to be captured by this process, which is also the case for catastrophic failure [22]. The two extreme cases are the nearest neighbor (R = 1) and mean-field (R L, where L is the system size) interactions and we find a crossover length scale R c above which the system starts behaving like the mean-field limit.…”
Section: Modelmentioning
confidence: 56%
“…Several attempts have been made to interpolate between these two limits [18][19][20][21][22]. However, in the case of catastrophic failures, the stress at which the system just breaks (critical stress) becomes non-zero only when the range of interaction is sufficiently large, so that it suppresses any spatial stress concentration [22]. Hence, statistics that are qualitatively similar to experiments [23] are observed only in the mean-field limit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that at the critical point, the relaxation time scales as τ ∼ N α , with α = 1/3 for b = 0 [25,29]. But for b > 0 the power law scaling seems to be lost, with τ becoming almost independent of N for b > 1 (see Fig.…”
mentioning
confidence: 97%
“…Both the number of clusters and the maximum cluster area stabilizes after some point as damage develops within the cohesive elements. Although the models are of different nature, an analysis using fiber bundle models showed that the statistics of successive broken fiber patches signal a similar nonmonotonic behavior [33].…”
Section: Damage Clustersmentioning
confidence: 99%